Stadscollectie 1989 Rotterdam : Verzameld werk 2. (Rotterdam : Museum Boymans van Beuningen, 1990)
Beckman, Paul ; Begeer, Piet ; Bieling, Herman ; Bouvé, Gesina ; Budding, Allard ; van de Camp, Geert ; Everse, Dook ; Ficheroux, Mathieu ; Franse, Kees ; van Golden, Daan ; Gijzen, Wim ; de Haas, Alex ; van Heusden, Wout ; Janssen, Edwin ; Kalksma, Gea ; van der Kraan, Axel en Helena ; van Lieshout, Joep ; Meijerink, Johan ; van Oord, Johan ; Oorebeek, Willem ; van Rest, Charlie ; Robèr, George ; de Ruiter, Guus ; Schafthuizen, Joop ; van Tiel Quirijn, Valdimarsson, Stefan A. ; van de Ven, Lidwien ; Verwey, Hans ; Westerik, Co ; Zegers, Ben
Stadscollectie 1989 Rotterdam : Verzameld werk 2, Museum Boymans-van Beuningen, Rotterdam, 29 april - 25 juni 1990
boek
Keywords: Rotterdam